Avaliação da atividade cicatrizante do extrato de Aloe vera L. em queimaduras de 3º grau experimentalmente provocadas em ratos - Guadalupe, Gisela Daleva Costa (2015)
Aloe vera gel is a very popularly plant used in burns treatment. This study aimed to evaluate the healing activity of Aloe vera L. gel provided by a cosmetics company in 3rd degree burns caused experimentally in rats. This study used 45 male Wistar rats, adults who were divided into 3 groups with 05 subgroups, each subgroup with n = 03. Group 1, treated with 1% silver sulfadiazine; group 2, treated with aqueous solution containing 1% preservative from the Aloe vera gel and group 3, treated with 98% Aloe vera gel. The animals were anesthetized, undergo shaving and cleaning the cervical dorsal region with saline solution and burn injury 3rd degree with 4cm² using boiling water to about 96 C in contact with the animal's skin for 14 seconds. The animals received an occlusive dressing on all experimental days. The wounds were evaluated on the 3rd, 7th, 14th, 21st and 30th days after the burn and the animals were euthanized for morphological, macroscopic and microscopic analysis. The evaluation of macroscopic results, whose parameters were crust, hyperemia, granulation tissue and fibrosis were no statistically significant differences between groups 1, 2 and 3 when compared over time. Morphometry, which analyzed the wounds contraction degrees were also no statistically significant differences between groups 1, 2 and 3 in the evaluated periods. The evaluation of microscopic results found some statistically significant results in 3th day: hyperemia and fibroblasts were higher in group 1 when compared to group 2; on the 30th day , angiogenesis was higher in groups 2 and 3 , when compared to group 1. Other parameters: necrosis, hyperemia, hemorrhage, fibrin and collagen, showed no statistically significant differences when comparing the groups over time. The 98% Aloe vera gel of the present study did not show the expected efficacy in relation to the anti-inflammatory action and healing among the three groups compared the experimental days.